The Influence of Beauty Influencers, Electronic Word of Mouth, and Brand Image on Purchase Intention of Skintific Products in Bandar Lampung - Maulia Putri; Yuniarti Fihartini (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the influence of Beauty Influencers, Electronic Word of Mouth, and Brand Image on the Purchase Intention of Skintific products in Bandar Lampung. Skintific, a Canadian skincare brand, has gained popularity in Indonesia, especially among younger consumers, through social media-based digital marketing. The research employs a quantitative method with a descriptive approach. The population includes individuals in Bandar Lampung who are aware of and intend to purchase Skintific products. A purposive sampling technique was used to obtain 126 respondents. Data were gathered using a Likert-scale questionnaire and analyzed through multiple linear regression with SPSS software. The findings reveal that Beauty Influencer, Electronic Word of, and Brand Image each have a positive and significant effect on Purchase Intention, both partially and simultaneously. Among these variables, Electronic Word of has the most dominant influence, followed by Beauty Influencer and Brand Image. The coefficient of determination (R²) is 0.512, indicating that the three variables explain 51.2% of the variance in purchase intention, with the remaining 48.8% influenced by other factors. These results highlight the effectiveness of digital marketing through credible influencers, positive online reviews, and a strong brand image in driving consumer purchase intention.